Rapid Cognitive Decline and Recurrent Falls in a 71 Year-Old Man due to Cerebral Amyloidangiopathy-Related Inflammation (CAA-RI) - Dörr, Stefan (Geriatrics (Basel), 2019)
Cognitive decline and falls in the elderly are common and are often accepted as natural and inevitable by relatives and health care professionals, but frequently there are specific and treatable diseases that should be revealed. In our case, cerebral amyloid angiopathy-related inflammation (CAA-RI) was causative for neuro-psychiatric symptoms and worsening of gait in a 71 year-old man with recurrent falls and decline of gait and cognition. Cerebral amyloidangiopathy (CAA) is an important cause of cerebrovascular disorders in the elderly, characterized by leukoencephalopathy combined with lobar or small cortical hemorrhage due to amyloid deposition in cortical and leptomeningeal vessels. In several conditions, amyloid deposition can provoke inflammation or edema that lead to -normally reversible- encephalopathy. CAA-RI is then characterized by subacute neurobehavioral symptoms, headache, seizures or stroke-like signs. The first therapeutic option after confirming the diagnosis is treatment with glucocorticoids. Despite treatment with prednisolone, our patient could not regain his unrestricted mobility and self-help competence. Our report aims to sharpen awareness for CAA and its inflammatory form (CAA-RI) in healthcare professionals involved in medical care of the elderly and provide a short summary of this disease.